DAMPAK PERUBAHAN INTERAKSI SOSIAL MASYARAKAT DENGAN KEBERADAAN PT REZEKI KENCANA DI DESA SUNGAI DERAS KECAMATAN TELUK PAKEDAI - Nopriyana Tariyadi, Ika Erwin; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe title of this thesis is "The Impact of Changes in Social Interaction with the Existence of PT Rezeki Kencana in Sungai Deras Village, Teluk Pakedai District". The general problem in this study is how 1) The positive impact of changes in social interaction in the community of Sungai Deras Village, Teluk Pakedai District? 2) The negative impact of changes in social interaction in the community of Sungai Deras Village, Teluk Pakedai District? The method used is descriptive qualitative method. A sample of 5 people. Using interview and observation techniques. The results of the data analysis are: 1) The positive impact of social change in Sungai Deras Village, Teluk Pakedai Subdistrict, which still preserves the culture and customs of its old habits such as cooperation, mutual cooperation and mutual consultation which have important values for Sungai Deras Village, Teluk Pakedai District. 2) The negative impact of social changes in Sungai Deras Village, Teluk Pakedai Subdistrict, there are changes that occur within individuals starting with the conflicts that occur in community life such as differences of opinion, differences in understanding, advances in modern tools in society..Keywords: Changes in Social Interaction